Index of the Project Gutenberg Works of Thomas Dixon - Dixon, Thomas, Jr., 1864-1946; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2018)
"Index of the Project Gutenberg Works of Thomas Dixon" by Jr. Thomas Dixon is a compilation of various literary works written during the early 20th century. This book serves as a catalog of Dixon's diverse contributions, which include novels, historical romances, and social commentaries, often touching upon topics related to the American South, race relations, and the impact of the Civil War. The collection reflects the author$1 (Bs perspective on significant historical events and the characters shaped by them. The contents of the book feature several titles, including "The Clansman," "The Foolish Virgin," and "The Fall of a Nation," among others. Each entry provides insight into Dixon's exploration of themes such as love, morality, societal structure, and the complexities of human relationships against the backdrop of historical events. Works like "The Clansman" depict the post-Civil War South and the rise of the Ku Klux Klan, emphasizing the struggles of individuals caught in these tumultuous times. Overall, this index serves not just as a reference but as an invitation to engage with Dixon's narratives that interweave personal and collective histories. (This is an automatically generated summary.)s
Release date is 2018-10-28
Produced by David Widger
Keywords: Indexes